Waves in the Arabian Sea and the Bay of Bengal during the monsoon season - THIRUVENGADATHAN, A. (MAUSAM, 1984)
The wave da1a recorded over the Indian seas by the Russian research vessels during the ISMEX (Indo-Soviet Monsoon Experiment) of 1973 and the Monsoon Experiment of 1977 are analysed. It is found that for given wind speeds, wave heights remain practically the same, the scattering being quite small. This is probably because during the monsoon season, the steadiness of the wind is quite high and the fetch is quite large. An empirical relationship is obtained between the wind-speed and characteristic wave height. The relationship has been verified with the data of the Russian research vessels during Monex 1979. The wave heights computed from the reported windspeeds compare quite favourably with the observed values.